(untitled) (Economic studies journal, 2024)
The study aimed to identify the role of digital transformation in improving the Optimization performance of workers at Al-Madar Al-Jadeed Company in the city of Benghazi. It used the descriptive analysis approach, and a questionnaire newspaper was designed and distributed to the study sample of (80). A sample of employees of the company under study, and (65) questionnaires were retrieved, i.e. a percentage Recovery equal to (81%).Data were analyzed by statistical software(SPSS) One of the most important result reached is the existence of a statistically significant relationship between the dimensions of digital transformation (vision and strategic planning, human resources, infrastructure, information security) and improving the job performance of Al-Madar al-Jadeed Company’s employees. key words: Digital transformation, transformation performance, Al-Madar al Jadeed.